2016
DOI: 10.1111/zph.12339
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Respiratory Involvement in a Cluster of Brucella suis‐Infected Workers from a Pork Processing Plant in Argentina

Abstract: Summary Epidemiological and clinical aspects of Brucella suis infection in 17 workers from a pork processing plant in Argentina occurring between January 2014 and July 2015 are presented. All patients reported working 9 h daily without adequate personal protection garment. Blood cultures were positive for Brucella spp. in 14 of the 17 patients (82.3%). All isolates were identified as B. suis biovar 1. Although fever, sweats, asthenia, myalgia and hepatic involvement were the most frequent clinical manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…94 In 17 workers infected with B. suis at a pork processing plant in Argentina, 4 had indications of respiratory involvement and infections were assumed to be the result of aerosols, conjunctival splashes, or direct entry through skin lesions. 95 In similar manner to other reports of pulmonary brucellosis, patients in this study responded well to antimicrobial treatment with no relapses in patients with respiratory involvement. 95 In a survey of human brucellosis caused by B. suis in Australia, 38% (n = 12) had respiratory symptoms but the manuscript did not clarify if patients with respiratory symptoms were among the 9% (n = 3) that had relapse after treatment.…”
Section: Some Issues Related To Brucella Of Importance To Fesap Discusupporting
confidence: 89%
See 1 more Smart Citation
“…94 In 17 workers infected with B. suis at a pork processing plant in Argentina, 4 had indications of respiratory involvement and infections were assumed to be the result of aerosols, conjunctival splashes, or direct entry through skin lesions. 95 In similar manner to other reports of pulmonary brucellosis, patients in this study responded well to antimicrobial treatment with no relapses in patients with respiratory involvement. 95 In a survey of human brucellosis caused by B. suis in Australia, 38% (n = 12) had respiratory symptoms but the manuscript did not clarify if patients with respiratory symptoms were among the 9% (n = 3) that had relapse after treatment.…”
Section: Some Issues Related To Brucella Of Importance To Fesap Discusupporting
confidence: 89%
“…95 In similar manner to other reports of pulmonary brucellosis, patients in this study responded well to antimicrobial treatment with no relapses in patients with respiratory involvement. 95 In a survey of human brucellosis caused by B. suis in Australia, 38% (n = 12) had respiratory symptoms but the manuscript did not clarify if patients with respiratory symptoms were among the 9% (n = 3) that had relapse after treatment. 73 In conclusion, data suggest that localization in pulmonary tissues; even in environments in which exposure may have been via aerosol, is not associated with more severe clinical symptoms and responds equally well to antimicrobial treatment as compared to brucellosis patients without pulmonary involvement.…”
Section: Some Issues Related To Brucella Of Importance To Fesap Discusupporting
confidence: 89%
“…A total of 292 individuals working in slaughterhouses were described as brucellosis-positive in fourteen articles [19,20,23,33,34,[41][42][43][44][45][46][47][48][49]. Most of those individuals were from America (n = 162), Africa (n = 60), and Europe (n = 37) and the minority from Asia (n = 33).…”
Section: Abattoir Workersmentioning
confidence: 99%
“…Brucella is more common in cattle, sheep, pigs and other domestic animals, patients are mainly infected by contact with infected sheep or by drinking infected goat milk ,Brucella can also be transmitted from person to person, the most common vertical transmission between mother and child [12].The incubation period is usually 5-60 days [13].After infection, the symptoms of Brucellosis are atypical and the clinical manifestations are varied, including fever, bone and arthropathy, sweating, fatigue, etc., which can be combined with other diseases. Because of its characteristics, it is easy to cause clinical missed examination and misdiagnosis, so that the disease delay, and even cause arthritis, myocarditis, liver and spleen involvement and other complications [14][15][16].Lots of studies have shown that CRP and PCT are sensitive indicators for the diagnosis of Brucellosis [17,18].The cure rate of infection in the acute stage of brucellosis is 90-95%, and the chronic infection caused by brucellosis has not been cured, so early diagnosis, early treatment of brucellosis is very important. After 72 hours of blood culture, the culture system reported positive results.…”
Section: Discussionmentioning
confidence: 99%